Chilling and Drought Stresses in Crop Plants: Implications, Cross Talk, and Potential Management Opportunities - Hussain, Hafiz A.; Hussain, Saddam; Khaliq, Abdul; Ashraf, Umair; Anjum, Shakeel A.; Men, Shengnan; Wang, Longchang (Frontiers in Plant Science, 2018)
Plants face a combination of different abiotic stresses under field conditions which are lethal to plant growth and production. Simultaneous occurrence of chilling and drought stresses in plants due to the drastic and rapid global climate changes, can alter the morphological, physiological and molecular responses. Both these stresses adversely affect the plant growth and yields due to physical damages, physiological and biochemical disruptions, and molecular changes. In general, the co-occurrence of chilling and drought combination is even worse for crop production rather than an individual stress condition. Plants attain various common and different physiological and molecular protective approaches for tolerance under chilling and drought stresses. Nevertheless, plant responses to a combination of chilling and drought stresses are unique from those to individual stress. In the present review, we summarized the recent evidence on plant responses to chilling and drought stresses on shared as well as unique basis and tried to find a common thread potentially underlying these responses. We addressed the possible cross talk between plant responses to these stresses and discussed the potential management strategies for regulating the mechanisms of plant tolerance to drought and/or chilling stresses. To date, various novel approaches have been tested in minimizing the negative effects of combine stresses. Despite of the main improvements there is still a big room for improvement in combination of drought and chilling tolerance. Thus, future researches particularly using biotechnological and molecular approaches should be carried out to develop genetically engineered plants with enhanced tolerance against these stress factors.